Biology and Management of the Bermudagrass Mite, Eriophyes cynodoniensis - Pablo Agustin Boeri; Nicole D. Benda; Joseph Bryan Unruh; Adam G. Dale (EDIS, 2018)
The bermudagrass mite, Eriophyes cynodoniensis (Sayed) (Arthropoda: Arachnida: Eriophyidae), also known as the couch grass mite, can be a serious pest of bermudagrass in multiple high-maintenance turf systems such as sod production, athletic fields, and golf courses. Mites cause leaf and bud galls, which can lead to severe aesthetic damage and plant decline or death in high-maintenance areas with low tolerance for plant damage. In this 7-page fact sheet written by Pablo Agustin Boeri, Nicole D. Benda, J. Bryan Unruh, and Adam Dale and published by the UF/IFAs Entomology and Nematology Department, review the biology, identification, and management of the bermudagrass mite, and get specific management recommendations based on evidence from UF/IFAS research. https://edis.ifas.ufl.edu/in1217